Externalizing Behaviors in Preschool-Aged Children With Cochlear Implants. - Kronenberger, William G.; Castellanos, Irina; Beer, Jessica; Pisoni, David B. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Deaf children with cochlear implants (CIs) experience challenges in early development of hearing and language skills that may place them at risk for externalizing behavior problems, such as aggression, hyperactivity--impulsivity, and oppositional behavior. This study is a longitudinal investigation of (a) between-groups differences in externalizing behavior problems between preschoolaged children with CIs and normal-hearing (NH) peers, and (b) within-group factors that may explain variability in externalizing problems within the sample of CI users. Method: Parents of 26 children with CIs and 30 NH peers completed externalizing behavior checklists at two visits separated by 1 year, starting at ages 3 or 4 years. Demographic/hearing history variables, language (vocabulary), nonverbal intelligence, and coping flexibility were assessed for concurrent and predictive associations with externalizing problems within the CI sample. Results: Results showed significantly greater externalizing behavior problems in CI users compared to NH peers at Time 1, although these differences were less pronounced 1 year later. Poorer residual hearing and better coping flexibility at Time 1 were associated with fewer externalizing behavior problems in CI users at Time 2. CI users who showed improvement in coping flexibility over the 1- year period also showed improvement in externalizing behaviors during that period. Nonverbal intelligence and language were not associated with externalizing behavior problems. Conclusions: Preschool-aged CI users may be at greater risk than NH peers for the early development of externalizing behavior problems. Improved coping flexibility may offer the potential for improvement in externalizing behavior problems for young CI users.